ACADEMIC SUPPORT SOFTWARE DEVELOPMENT WITH ASP .NET CORE - Graciano, Fernando; Espirito Santo, Felipe do; Graciano, Marcos Danilo (Revista Interface Tecnológica, 2020)
With the high demand for multimedia equipment for classes in a teaching institution and the low demand for equipment for collective use, software that manages the reservation and use of the equipment is necessary. This demonstration file shows the necessary steps for the software development, architecture and implementation of a web application, which would facilitate access to teachers when requesting multimedia equipment. The implementation of the software provides an organization like equipment reservations and facilitated access to the system via the internet from anywhere and also through mobile devices. No development process was used Mysql as a database management system, Asp network core and shaving pages for the development of the application. After the implantation, there was an improvement in the organization of equipment reserves for the support team, both in the installation in the classrooms and in the removal and preparation for the next use. Teachers also felt an improvement in their use compared to the legacy system, which did not allow access from outside the institution, much less from mobile devices.